KECURANGAN LAPORAN KEUANGAN, LAPORAN KEUANGAN, MANIPULASI LABA, MODEL M-SCORE BENEISH - isna, isnawati; Effendy, Lukman; Isnaini, Zuhrotul (Jurnal Riset Akuntansi, 2024)
The M-Score strategy (Beneish, 1999) is widely used as a financial forensic tool in detecting financial statement fraud (Buljubasic & Halilbegovic, 2017; Hasan et al., 2017), but this study has not found evidence during a crisis. Therefore this study attempts to fill this gap by conducting research in selected Asian countries such as Malaysia, Indonesia, Thailand, Hong Kong, Singapore, China and Japan. The aim to find empirical evidence about the percentage of financial statements that were manipulated during the Covid-19 crisis (2020 and 2021), the manipulation index and what techniques are often used in manipulating financial reports during the crisis. The results found empirical evidence that there were indications of financial statement manipulation during a crisis (the M-Score result) was very high at 94.8%, but the overall manipulation index (OMI) was even lower at 39% compared to what was found. by Hassan et. al (2017) of 72%. The technique most often used by companies to commit fraudulent financial statements during a crisis is the TATA variable, that maximizing the value of accruals (other than cash). Furthermore, the results are also in line with the results of previous studies which found significant differences between countries in terms of financial statement manipulation.